Child Poverty and Family Structure during the Recession in English-Speaking Liberal Welfare States - David W. Rothwell; Annie McEwen (Luxembourg Income Study (LIS), 2016)
While the 2008 global economic crisis is over and many countries are into a recovery phase, the impacts continue to linger. Analysis of its aftermath offers insight into how economic shocks reverberate through modern economies to affect the lives of children and families and how governments respond to economic crises. We calculate child poverty rates before and during the Great Recession in five nations - Australia, Canada, Ireland, the United Kingdom and United States. Data are from the latest nationally representative and harmonized household survey data available from the LIS Cross-National Data Center (Waves VII and VIII, approximately aligning with years 2007 and 2010). The study adds new knowledge in several ways. Welfare policies of the selected countries share common reliance on means-tested social assistance, higher economic inequality, and less unionization. While prior studies have examined within-country and cross-country variation in child poverty outside of the Recession, this paper investigates variation within welfare regime during a crisis. Second, within each country, we quantify the impact that market, social policy transfers, and taxes had on child poverty. Last, within countries, we examine how children's family structure affected their chances of living in poverty. We find large variations in child poverty rates during this period. Using a poverty threshold anchored in the 2007 distribution, across countries child poverty increased the most in Ireland and Australia and decreased the most in the UK and Canada. The US experienced only marginal changes in child poverty. Within countries, we find that children in married families have the lowest risk of poverty, except for the UK where the probability of being poor was lower for single and cohabitating families. Decomposing poverty rates by income source (labor, transfers, and taxes) over time, we quantify the contribution to the change in poverty rate. Labor earnings explained the poverty reduction in Canada and UK changes in poverty occurred primarily via transfers. In the US, the transfer system offset what would have been a large increase in poverty (4-percentage point). We then disaggregate these changes within country by family structure, finding significant variations in how earnings and social transfers affected children. Together, these findings document the impact of the different levels of cushioning provided by liberal welfare states in the Great Recession and the resulting differing relative poverty risks of different family structures.
Keywords: 330; social policy; recession; child poverty; liberal welfare states; child policy; family policy